Participatory Observation Approach Participatory Rural Appraisal Method in Formulating Development Guidelines for the Lakkang Delta Area as a Tourism Destination - Mukti Ali; Arifuddin Akil; Ihsan .; Wiwik Wahidah Osman; Marly Valenti Patandianan; Yashinta Kumala Dewi; Sri Aliah Ekawati; Isfa Sastrawati; Muhammad Irfan; Gafar Lakatupa; Nur Jayadi; Ahmad Saiful Munir; Andi Dinda Maharani; Andi Habib Makalang (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
The Lakkang Delta area in Tallo District, Makassar City, is a unique small island surrounded by the Tallo and Pampang Rivers, presenting the character of a ‘village in the middle of the city’ with high ecological, social and cultural potential. However, limited accessibility, basic infrastructure and tourism institutions mean that its potential has not been optimized. This community service activity was carried out in Lakkang Village, Tallo District, Makassar City, involving 30 participants consisting of the community, village officials, and representatives of tourism awareness groups. This activity aimed to develop guidelines for the development of the Lakkang Delta area as a community based ecotourism destination using the Participatory Rural Appraisal (PRA) method. This method includes participatory mapping, transect walks, in-depth interviews, and door-to-door socialization to explore local potential and actual problems in the field. The activity was evaluated through pre-test and post-test to measure the community's level of understanding of the concepts of ecotourism and spatial-based planning. The results showed a significant increase in the average understanding score from 60 to 85 (an increase of 41.6%). The main identified potentials were bamboo forests, fishponds, and Japanese bunker historical sites, as well as the social value of mutual cooperation. The main issues included transportation access, basic infrastructure, and tourism management institutions. This activity had a direct impact on increasing the community's capacity to manage tourism potential, the creation of a participatory potential map, and recommendations for development strategies aligned with the Makassar City Spatial Plan (RT/RW) 2024–2043. Thus, this activity demonstrated the effectiveness of the PRA method in promoting active participation and ecological awareness among the community.